Exploring Parental Responses to Pre-schoolers’ “Everyday” Pain Experiences Through Electronic Diary and Ecological Momentary Assessment Methodologies - O’Sullivan, Grace; McGuire, Brian; Roche, Michelle; Caes, Line (Frontiers in Psychology, 2021)
Objective: Parental influence during children’s “everyday” pain events is under-explored, compared to clinical or experimental pains. We trialled two digital reporting methods for parents to record the real-world context surrounding their child’s everyday pain events within the family home. Methods: Parents (N=21) completed a structured e-diary for 14 days, reporting on one pain event experienced by their child (aged 2.5-6 years) each day, and describing child pain responses, parental supervision, parental estimates of pain severity and intensity, and parental catastrophizing, distress, and behavioural responses. During the same two-week period, a subsample of parent-child pairs (N=9) completed digital ecological momentary assessments (EMA), immediately after any chosen pain event. Children reported their current pain while parents estimated the child’s pain and indicated their own distress. Results: ‘Everyday’ pain events frequently featured minor injuries to the child’s head, hands or knees, and child responses included crying and non-verbal comments (e.g., “Ouch!”). Pain events occurred less frequently when parents had been supervising their child, and supervising parents reported lower levels of worry and anxiety than non-supervising parents. Child sex was significantly associated with parental estimates of pain intensity, with parents of girls giving higher estimates than parents of boys. Child age was significantly associated with both the number of pain events and with parental estimates of pain intensity and child distress: the youngest children (2-3 years) experienced the fewest pain events but received higher pain and distress estimates from parents than older children. Hierarchal Linear Modelling revealed that parental estimates of pain severity were significant positive predictors of parental distress and catastrophizing in response to a specific pain event. Furthermore, higher levels of parental catastrophic thinking in response to a specific pain event resulted in increased distress, solicitousness, and coping-promoting behaviours in parents. The EMA data revealed that children reported significantly higher pain intensity than their parents. Conclusions: The electronic pain diary provided a key insight into the nature of “everyday” pain experiences around the family home. Digital daily reporting of how the family copes with “everyday” events represents a viable means to explore a child’s everyday pains without disrupting their home environment.